A "MESOSIDERITE" ROCK FROM NORTHERN SIBERIA, RUSSIA: NOT A METEORITE - Treiman A.H.; Lindstrom D.J.; Schwandt C.S.; Franchi I.A.; Morgan M.L. (My University, 2002)
A possible mesosiderite meteorite was found in the area of the Putorana Plateau, Noril'sk district, Siberia, Russia. Although this rock resembles a mesosiderite in its hand-sample aspect and in having Ni-bearing iron metal, it is not a meteorite. This inference is based on the lack of a fusion crust, the lack of cosmogenic nuclides, oxygen with terrestrial isotope ratios, and several mineral chemical criteria. Most likely, the rock is from the iron-metal-bearing basalts of the Siberian Trap basalt sequence, which are mined for their base and platinum-group metals. Mesosiderite imposters like this may be recognized by: (1) the presence of Cu metal in hand sample or as microscopic blebs in the low-Ni metal (kamacite), (2) the absence of high-Ni metal (taenite), and (3) the presence of iron carbide (cohenite) enclosing the kamacite. Even if these macroscopic tests are inconclusive, isotopic and mineral chemical tests will also distinguish rocks like this from mesosiderites.